Engaging employees for quality of life: mediation by psychological capital. Issue 5 (26th April 2019) - Gupta, Manish; Shaheen, Musarrat; Das, Manoj
ABSTRACT: The objective of this study is to examine the mediating role of psychological capital (PsyCap) between work engagement and the six dimensions of quality of work life (QoWL). Data were collected from the employees working in the accident and emergency department of tertiary hospitals in India involved in rendering emergency healthcare services. Structural analysis showed that PsyCap fully mediates the relationship between work engagement and control at work and partially between work engagement and the other five dimensions of QoWL. These results augment broaden and build theory by explaining the role of PsyCap in channelizing the positive effect of work engagement to improve employees' QoWL. Hospitals with the accident and emergency department are encouraged to recruit psychologically capable employees. Such employees can transfer the benefits of their personal resources and engagement to the quality of life at work and be less prone to burnout.